Operations Management Strategy To Improve Efficiency And Service Quality Through Decision Support System - Lestari Pratiwi Sitanggang; Ayu Trisanti; Ritawati Sirait; Pandapotan Sitompul; Donalson Silalahi (SEAN Institute, 2025)
This research explores the operations management strategies implemented to improve operational efficiency and service quality in Cooperative “XYZ” as well as the hospitality sector in Samosir Regency. With a descriptive analytical approach and secondary data support from performance reports, customer satisfaction surveys, and academic literature, it was found that strategies such as information technology utilization, capacity planning, and supply chain management made significant contributions. The utilization of a decision support system (DSS) enables more targeted data-driven decision-making. The results showed that the utilization of information technology increased operational efficiency by 30% and customer satisfaction reached 86.7%. The utilization of SPK places alternative technology utilization strategies as a top priority for optimizing operational performance and customer satisfaction.